Relationship beetwen Perception, Motivation and Characteristic of Nurses with the Implementation of the Hand Hygiene - Br. Karo, Mestiana; Barus, Mardiati; Tumanggor, Agnes (Universitas Airlangga, 2019)
Introduction: Nosocomial infection is a cross infection that occurs due to the displacement of microorganisms through health workers and tools used when taking action. The most effective way to prevent nosocomial infections is to run universal precaution, one of which is by washing the hands on each handling hospital patients. The purpose of this study was to study the relationship of perceptions, motivations, and characteristics of nurses with hand hygiene in the internist room in the hospital.Method: The type of research was observational analytic and simple random sampling technique. The independent variables were perception, motivation, and characteristics of nurses. The dependent variable was the hand hygiene. The sample of the research was 132 nurses at Santa Elisabeth Hospital, Medan. The data was collected using a questionnaire. The analysis used a multiple linear regression test.Result: The result of the study obtained that there was a correlation between perception with implementation hand hygiene with the value p = 0,005 < α= 0,05. There was a relationship between characteristics with implementation hand hygiene with a value of p = 0,002 < α= 0,05. There was a correlation between motivation with the implementation of hand hygiene with a value of p = 0,001 < α= 0,05.Conclusion: Hospital Santa Elisabeth Medan will be better terrain for increase and infrastructure support in the implementation of the or the ability students in implementing activities prevention nosocomial infections to others and patients.